(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess the effectiveness of a nutritional product administered over a three-month intervention period in improving picky eating behaviors and reducing upper respiratory tract infections among young children. Methods: A community-based randomized controlled intervention study was conducted among 603 children aged 2-4 years in Phu Binh district, Thai Nguyen province. Participants were randomly allocated into two groups. The intervention group received 50g of a high-energy nutritional product twice daily, containing vitamins B1, B2, B6, and B9 at levels providing 85-140% of the recommended dietary intake. The control group continued their usual diet without supplementation. Results: Following the three-month intervention, the intervention group demonstrated significant improvements in picky eating status. The prevalence of picky eating decreased from 66.8% to 47.2% in the intervention group, compared with a reduction from 72.8% to 57.9% in the control group, with the between-group difference being statistically significant (p < 0.01). Conclusion: A three-month supplementation with an energy-dense, micronutrient-enriched nutritional product was effective in improving picky eating behaviors among preschool children.